Effects of covid-19 and strategies employed by entrepreneurs in the Peruvian gastronomic sector during the pandemic - Karla Soria-Barreto; Gianni Romaní; Guillermo Peralta-Godoy; Rafael Flores-Goycochea; Eduardo Ruiz-Sevillano (Fórum Empresarial)
This study investigates the impact of the coronavirus disease of 2019 (COVID-19) pandemic on the gastronomic sector in Lima, Peru. The theory of dynamic capabilities an appropriate theoretical framework for analyzing how Peruvian gastronomic entrepreneurs have adapted and responded effectively to the challenges imposed by the COVID-19 pandemic. Through questionnaires and in-depth interviews, the study examines response strategies these businesses adopted to mitigate pandemic consequences. The findings reveal a significant sales reduction as the pandemic’s primary effect, attributed to reduced customer traffic due to government-imposed quarantines. Marketing strategies, operational shifts, and cost reductions were common survival tactics. Despite challenges, the study underscores the gastronomy sector’s adaptability, creativity, and preparedness in navigating the crisis. Practical implications include the importance of crisis management planning.